Chris Keith, Jesus’ Literacy. Scribal Culture and the Teacher from Galilee (Library of New Testament Studies 413 – Library of Historical Jesus Studies 8; London et al.: Bloomsbury, 2013) - Kubiś, Adam (The Biblical Annals, 2016)
Book review: Chris Keith, Jesus’ Literacy. Scribal Culture and the Teacher from Galilee (Library of New Testament Studies 413 – Library of Historical Jesus Studies 8; London et al.: Bloomsbury, 2013). Pp. XVI + 224. GBP 17.99. ISBN 9780567533975 (Paperback).